2021
DOI: 10.1097/oi9.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcomes of pediatric supracondylar humeral fractures in Korle Bu Teaching Hospital

Abstract: Objectives: Supracondylar humeral fractures (SCHF) are the most common elbow injury in the pediatric population. The treatment, outcome, and health-related quality of life (HRQoL) following these injuries are described. Methods: Patients with SCHF who were treated depending on the fracture type were evaluated. Medical records stored in the REDCap database were reviewed to obtain information on demographics, mechanisms of injury, neurovascular status, infection rates, and postoperative complications. Outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“… 12 , 13 Neurovascular injury can lead to long-term disabilities and the cost of managing complications could go up to five times or more compared to the cost of the initial management. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 Neurovascular injury can lead to long-term disabilities and the cost of managing complications could go up to five times or more compared to the cost of the initial management. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Neurovascular injury can lead to long-term disabilities and the cost of managing complications could go up to five times or more compared to the cost of the initial management. 13,14 Radiographic evaluation of the stage of a supracondylar humerus fracture is of paramount importance in the management of SCF of the humerus. 3,15 The lateral radiograph should be taken with the patient's arm flexed at a 90degree angle, the humerus horizontal and the elbow on the same plane with the shoulder and the wrist being in a lateral position.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the mechanism of injury, there is a notorious predominance of extension-type injuries. In a study of 159 patients, Barr [ 14 ] found that 155 presented extension-type injuries, and Baidoo et al [ 15 ] described that 96% of fractures were of the extension type. These findings are consistent with those of our study, which showed that flexion-type fractures are a rare entity, accounting for less than 2% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of our study, which showed that flexion-type fractures are a rare entity, accounting for less than 2% of the cases. In relation to the affected side, the referenced studies coincide in showing a predominance of the non-dominant side [ 13 - 15 ]. The present study found that 62% of injuries occurred on the left side, in line with the results described by Poulios et al [ 13 ] and Baidoo et al [ 15 ] in their publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation